Studi Kasus Analisis Pendapatan Usaha Keripik Kalakai Imur di Kota Palangka Raya - Asro Laelani Indrayanti; Nurul Hidayati; Nanang Hanafi (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2016)
Kalakai containing compounds or substances that included a functional food. One way is the use of plants kalakai processing into chips kalakai. Processed chips kalakai located in the city of Palangka Raya one of which is Imur. The purpose of this study was to determine the production cost of chips kalakai imur, knowing revenue kalakai imur chips and determine the efficiency of the chips kalakai imur. This research was conducted in Jl. Manjuhan city of Palangka Raya. When the study will take place over four (4) months. From the results of analysis show that (1) the cost of production of chips kalakai imur Rp. 10,141,200.00 during the period (per month), (2) income kalakai imur chips during the period (per month) Rp. 14.400.000,00, (3) Income/profit business kalakai imur chips during the period (per month) Rp. 4.258.800,00 (4) Efficiency of 1.4 imur kalakai chips.